2013
DOI: 10.1371/journal.pone.0067553
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Mapping Antigenic Epitopes of NS1 Protein of Japanese Encephalitis Virus with Monoclonal Antibodies

Abstract: Japanese encephalitis virus (JEV) non-structural protein 1 (NS1) contributes to virus replication and elicits protective immune responses during infection. JEV NS1-specific antibody responses could be a target in the differential diagnosis of different flavivirus infections. However, the epitopes on JEV NS1 are poorly characterized. The present study describes the full mapping of linear B-cell epitopes in JEV NS1. We generated eleven NS1-specific monoclonal antibodies from mice immunized with recombinant NS1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The JEV SA14 strain was propagated and titrated onto BHK-21 cells. Mouse monoclonal antibodies against the JEV prM (31,32), E (33), and NS1 (34,35) proteins were generated previously. Mouse monoclonal antibody against JEV NS2B was a gift from Shengbo Cao (Huazhong Agricultural University, Wuhan, China).…”
Section: Methodsmentioning
confidence: 99%
“…The JEV SA14 strain was propagated and titrated onto BHK-21 cells. Mouse monoclonal antibodies against the JEV prM (31,32), E (33), and NS1 (34,35) proteins were generated previously. Mouse monoclonal antibody against JEV NS2B was a gift from Shengbo Cao (Huazhong Agricultural University, Wuhan, China).…”
Section: Methodsmentioning
confidence: 99%
“…The inability of dengue serological assays to specifically identify dengue serotypes is a result of cross‐reactivity reactions between serotypes and other related flaviviruses . Dengue shares similar NS1 epitope sequences with JEV, WNV, and ZIKV . Within the four serotypes of dengue, it was also previously reported that sequence homology may reach up to 70% .…”
Section: Discussionmentioning
confidence: 99%
“…(19) Thus far monoclonal antibodies against the NS1 protein of Japanese encephalitis virus have been developed, and five B-cell epitopes have been screened by using them, which lays the foundation for further study of the antigenic structure of NS1 protein and the potential clinical application of epitope-based methods. (20) The development of monoclonal antibodies against NS1 protein of dengue virus has provided an effective tool for early diagnosis and classification of dengue virus infections clinically. The function of NS1 protein and mechanism of protein-protein interaction, once ascertained, may ultimately lead to the production of effective antiviral agents.…”
Section: Discussionmentioning
confidence: 99%